The effect of therapeutic regimen education on improving the self-efficacy in cancer patients undergoing haemodialysis: a quasi-experimental study - Susilowati, Indah; Nuraini, Tuti; Gayatri, Dewi; Afiyanti, Yati (Jurnal Ners, 2024)
Introduction: Cancer treatments often comes with varying adverse effects on both functional and physiological status of cancer patients, such as reduced kidney function, necessitating haemodialysis. The aim of this study was to determine the effect of therapeutic regimen education on the treatment self-efficacy of cancer patients undergoing haemodialysis. Methods: This study used a quasi-experimental method, involving 136 participants divided into control and intervention groups. The intervention group was given therapeutic regimen education that lasted for 4 weeks. The self-efficacy score was measured before and after intervention in both groups. Pre- and post-intervention scores were measured using the Chronic Kidney Disease Self-Efficacy instrument (r = 0.845). Paired t-test and independent t-test were used, respectively. Results: The results show that the patients who received therapeutic regimen education had significant increases in self-efficacy scores (p < 0.001). The mean (SD) score for all sub-variables increased after treatment: autonomy, from 15.07 (4.29) to 26.50 (1.74); personal integrity, from 11.63 (3.92) to 23.68 (2.59); problem-solving, from 10.66 (3.98) to 18.85 (0.82); and seeking social support, from 7.13 (2.38) to 14.06 (1.62). From the statistical test results, a significant difference in each dimension of self-efficacy was found between before and after treatment (p < 0.001). When the post test scores between intervention and control were compared, it showed significant different between them (p < 0.001). Conclusions: Therapeutic regimen education can increase treatment self-efficacy in cancer patients undergoing haemodialysis treatment, which can affect the patient’s healing process. Keywords: cancer patients, haemodialysis, self-efficacy, therapeutic regimen education